Analisis Korosi pada Elektroda Discharge di Sistem Electrostatic Precipitator (ESP) Pada Boiler dan Pengaruhnya terhadap Kinerja Listrik - Bayu Pradana; Siti Anisah; Haris Gunawan (CV. Hawari, 2026)
The Electrostatic Precipitator (ESP) is a critical component for particulate emission control in industrial boiler systems. ESP performance is strongly influenced by the condition of discharge electrodes, which are responsible for generating corona discharge and gas ionization processes. During long-term operation, the electrodes are exposed to hot flue gas, moisture, and corrosive compounds from shell combustion, leading to corrosion and surface degradation that may reduce electrical performance. This study aims to analyze the corrosion condition of discharge electrodes in an ESP installed on a 24 ton/h palm-shell-fired boiler and its effect on electrical performance, particularly operating voltage and current. The research employed visual inspection of electrode surfaces, interviews with maintenance personnel, and monitoring of electrical parameters from the transformer–rectifier panel before and after mechanical cleaning and surface coating. A comparative analysis was conducted to evaluate performance changes resulting from electrode maintenance. The results indicate that corroded electrodes significantly decreased secondary current and operational stability of the ESP. After cleaning and coating, the secondary current increased by up to 254%, the conduction angle became more stable, and overall ESP performance improved substantially. These findings demonstrate that corrosion mitigation and periodic electrode maintenance are essential for maintaining ESP electrical reliability and effective particulate emission control in industrial boilers.